2017
DOI: 10.1371/journal.pone.0175803
|View full text |Cite
|
Sign up to set email alerts
|

The metabolic basis of cognitive insight in psychosis: A positron emission tomography study

Abstract: The purpose of this study was to investigate the relationship between cognitive insight and cerebral metabolism in patients suffering from psychosis. The Beck Cognitive Insight Scale (BCIS) was administered to 63 patients with psychosis undergoing Positron Emission Tomography investigation. The sample was divided into two groups considering the BCIS score. Data were analyzed using Statistical Parametric Mapping. Results: patients with low insight, compared to those with high insight, showed decreased metabolis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
6
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 104 publications
4
6
0
Order By: Relevance
“…35 Moreover, a previous PET study from our group found metabolic alterations in this area in relation to insight towards the disease in a sample of psychotic BD patients and patients with schizophrenia. 36 Taken together, our results further suggested that alterations in regions associated with emotional processing may be considered a key feature of BD, as consistently reported by previous imaging studies in mood disorders. 37 However, although deficits in temporal cortex and insula are extensively found in BD, the role of occipital cortex in this disabling disorder is still not fully understood.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…35 Moreover, a previous PET study from our group found metabolic alterations in this area in relation to insight towards the disease in a sample of psychotic BD patients and patients with schizophrenia. 36 Taken together, our results further suggested that alterations in regions associated with emotional processing may be considered a key feature of BD, as consistently reported by previous imaging studies in mood disorders. 37 However, although deficits in temporal cortex and insula are extensively found in BD, the role of occipital cortex in this disabling disorder is still not fully understood.…”
Section: Discussionsupporting
confidence: 89%
“…Also, a recent MRI study showed that a history of psychosis in BD patients was associated with decreased GM volume in fusiform cortex . Similarly, a recent PET study carried out by our research group found that in psychotic BD subjects the presence of low insight of disease was associated with decreased metabolism in the fusiform gyrus along with other brain areas, such as precuneus, superior temporal gyrus and insula …”
Section: Discussionsupporting
confidence: 66%
See 3 more Smart Citations